Advanced network reconfiguration system applied to CEMIG-D system - Cavalcante, Patricia L.; Franco, John F. [UNESP]; Rider, Marcos J. [UNESP]; Garcia, Ariovaldo V.; Martins, Luana L.; Malveira, Marcos R. R.; Franco, Romulo J.; Carvalho, Paulo F. S.; Guimaraes, Daniel S.; Luiz, J. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
In the network reconfiguration context, the challenge nowadays is to improve the system in order to get intelligent systems that are able to monitor the network and produce refined information to support the operator decisions in real time, this because the network is wide, ramified and in some places difficult to access. The objective of this paper is to present the first results of the network reconfiguration algorithm that has been developed to CEMIG-D. The algorithm's main idea is to provide a new network configuration, after an event (fault or study case), based on an initial condition and aiming to minimize the affected load, considering the restrictions of load flow equations, maximum capacity of the lines as well as equipments and substations, voltage limits and system radial operation. Initial tests were made considering real data from the system, provided by CEMIG-D and it reveals very promising results. © 2013 IEEE.
Keywords: automatic reclosers; Power distribution system reconfiguration; power flow; smart grid; Automatic reclosers; Load flow equations; Network configuration; Network re-configuration; Operator decisions; Power distribution system; Power flows; Smart grid; Electric load distribution; Intelligent systems; Smart power grids